2006
DOI: 10.1105/tpc.106.044305
|View full text |Cite
|
Sign up to set email alerts
|

Tic21 Is an Essential Translocon Component for Protein Translocation across the Chloroplast Inner Envelope Membrane

Abstract: An Arabidopsis thaliana mutant defective in chloroplast protein import was isolated and the mutant locus, cia5, identified by map-based cloning. CIA5 is a 21-kD integral membrane protein in the chloroplast inner envelope membrane with four predicted transmembrane domains, similar to another potential chloroplast inner membrane protein-conducting channel, At Tic20, and the mitochondrial inner membrane counterparts Tim17, Tim22, and Tim23. cia5 null mutants were albino and accumulated unprocessed precursor prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 33 publications
4
155
0
Order By: Relevance
“…By thorough screening of antisera, we found that an antibody against Arabidopsis Tic21 caused a significant shift in this assay when Arabidopsis chloroplasts were used ( Figure 5A, lane 2). Tic21 was recently identified by Arabidopsis genetics (Teng et al, 2006). When antibodies against pea Tic110 and SPA-820 monoclonal antibody (StressGen), which recognizes an as yet unidentified intermembrane space Hsp70 (Schnell et al, 1994;Becker et al, 2004), were added, the mobility of the 1-MD complex on BN-PAGE was not affected ( Figure 5A).…”
Section: Tic21 Is Involved In the 1-md Translocation Complexmentioning
confidence: 93%
See 3 more Smart Citations
“…By thorough screening of antisera, we found that an antibody against Arabidopsis Tic21 caused a significant shift in this assay when Arabidopsis chloroplasts were used ( Figure 5A, lane 2). Tic21 was recently identified by Arabidopsis genetics (Teng et al, 2006). When antibodies against pea Tic110 and SPA-820 monoclonal antibody (StressGen), which recognizes an as yet unidentified intermembrane space Hsp70 (Schnell et al, 1994;Becker et al, 2004), were added, the mobility of the 1-MD complex on BN-PAGE was not affected ( Figure 5A).…”
Section: Tic21 Is Involved In the 1-md Translocation Complexmentioning
confidence: 93%
“…First, we performed transient expression and targeting of preproteins using Arabidopsis knockout mutants. Because both homozygous tic21/pic1 and tic20 mutants show severe albino phenotypes (Teng et al, 2006), standard import experiments using isolated plastids are difficult. Therefore, we used transient expression system in protoplasts (Jin et al, 2001;Lee et al, 2008).…”
Section: Immunodepletion Experiments Suggest That Tic20 Is Associatedmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter was proposed by Teng and co-workers (2006) as the third potential protein-conducting channel at the inner membrane of chloroplasts. This notion was disputed in another study, where the reported Tic21 (Teng et al , 2006 ) most likely represents an ancient metal permease, which regulates iron uptake and metal homeostasis in chloroplast and not a protein conducting channel (Duy et al , 2007 ). Despite the occurrence of several proteinconducting channel candidates for the inner membrane of the chloroplast, considerable lines of evidence clearly pinpoint Tic110 as the central subunit of the TIC complex, forming a high-conductance cation-selective channel Balsera et al , 2009 ).…”
Section: The Tic Complex: a Short Glimpsementioning
confidence: 97%